Analisis Pengaruh Job Insecurity, Dan Kompensasi Finansialterhadap Kepuasan Kerja Dan Turnover Intention: (Studi Pada Karyawan Kontrak Di Bali Dynasty Resort) - Devi, Ni Luh Mita Sri; Sudibia, Gede Adnyana (E-Jurnal Manajemen; Vol 4 No 4 (2015), 2015)
This study aimed to analyze the effect of job insecurity and financial compensation to job satisfaction and turnover intention of employees contract in Bali Dynasty Resort. This study uses 79 respondents to take the respondents of permanent employees and contract employees. Testing was conducted using path analysis technique (Path Analysis), Based on the analysis concluded variable job insecurity has a positive and significant effect on job satisfaction, job insecurity variable has a negative and significant effect on job satisfaction, financial compensation positive effect on job satisfaction, variable financial compensation has a negative and significant effect on turnover intention, job satisfaction variable has a negative and significant effect on turnover intention. Implementation of this research is that to avoid the desire of employees to find new jobs in other companies can be done by applying the career path for employees to contract employees feel that their work has more advantages in the future
Keywords: Job Insecurity, Kompensasi Finansial, Kepuasan Kerja, Turnover Intention